Ground reaction force of table tennis players when using forehand attack and loop drive technique - Yuqiang, D.; Xiaodong, Z.; Dandan, X. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The subjects were 10 excellent ping-pong players in China. The table tennis techniques of the forehand attack and forehand loop drive were tested, using the measurement methods of the KISTLER force-plate system. The results showed that the biggest GRF of the attack technique in vertical direction was higher than the loop drive technique, and the biggest GRF of the attack technique in left-right direction and the fore-aft direction were mostly lower than the loop drive technique.